Formulasi Strategi pada Agroindustri UMKM Klaster Unggulan Guna Pengembangan Ekonomi Lokal di Kabupaten Wonogiri - Wardani, Irma; Dewi, Tria Rosana (Universitas Galuh, 2025)
The development of regional autonomy through local agricultural resources needs to pay attention to regional specificities. Wonogiri Regency is one of the areas in Central Java that has potential to be developed into an agro-industrial sector focused on synergy in improving the regional economy based on local agricultural resources. Agro-industry through a cluster approach is able to have high performance and increase economic competitiveness. The aim of this research is to find out the right strategy options for the regional superior UMKM Agroindustry cluster to support the economy of the Wonogiri Regency region and provide benefits to the government in formulating policies. The research method used is qualitative descriptive analysis consisting of the AHP and SWOT methods. The results of research carried out using the AHP (Analysis Hierarchy Process) method in the regional superior cluster UMKM Agroindustry are Cashew Cluster (0.3817), Sweet Potato Cluster (0.12362), Processed Food Cluster (0.1331), Wood Cluster (0 .1305), Medicinal Plants Cluster (0.1208), Horticulture Cluster (0.0992). The highest results show the regional superior cluster in Wonogiri Regency, namely the Cashew Cluster. The results of the IE matrix analysis position the Cashew Cluster UMKM Agroindustry in cell IV, namely growth and development. The strategies that can be implemented are market penetration, market development and product development.